The assesment of trihalomethane levels in drinking water - Mohamed, Maketab; Jab, Ahmad Tajudin (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1992)
The growth of industry in Malaysia has caused several conflicts with the water resources management. Poor planning resulted in the siting of polluting industries and housing areas in critical watersheds that also provide potable drinking water to the general public. The chlorination of water with high organic waste, natural or anthropogenic, is detrimental to the health of the public as the trihalomethanes (THMs) produced are known to be carcinogenic.